Cyber Ethics and Digital Compliance in Malaysia: Empowering Ethical Digital Citizenship - Hamid, Elisnorazmaliza Ab; Mutalib, Roshila Abdul; Semail, Saifuddin (Tropical Scientific Journal, 2026)
Objective: This study investigates the relationship between cyber-ethics knowledge and digital-ethics compliance among Malaysian digital users. It addresses a key research gap, as past studies have focused predominantly on students, with limited empirical evidence involving adult digital users across diverse backgrounds. The study further aligns with national digital-transformation agendas and global sustainability goals, particularly SDG 4 (Quality Education), SDG 9 (Industry, Innovation and Infrastructure), and SDG 16 (Peace, Justice and Strong Institutions). Research Method: A quantitative survey design was employed using a structured online questionnaire distributed to 392 Malaysian digital users aged 18 and above. The instrument was developed based on the NIST Cybersecurity Framework and validated through expert review and pilot testing. Reliability analysis showed high internal consistency (overall Cronbach’s alpha = 0.914). Descriptive statistics were used to assess construct levels, while Pearson’s correlation analysis examined the relationship between cyber-ethics knowledge and digital-ethics compliance. The study tested both a null hypothesis (H₀: no significant relationship) and an alternative hypothesis (H₁: significant positive relationship). Findings: Results indicated high levels of cyber-ethics knowledge (M = 4.187, SD = 0.715) and digital-ethics compliance (M = 4.205, SD = 0.613). A strong, positive, and statistically significant correlation was found between the two constructs (r = 0.696, p < 0.001). These findings confirm that individuals with higher ethical knowledge are more likely to demonstrate responsible online behaviour, thereby supporting H₁ and rejecting H₀. Minor gaps were identified in fact-checking and responsible content sharing, indicating the need for continuous ethical reinforcement through education and policy. Originality: This study contributes new empirical evidence by focusing on adult digital users in Malaysia, extending existing literature beyond student-centred research. It strengthens theoretical understanding of digital citizenship by demonstrating that ethical literacy is a key determinant of ethical behaviour in online environments. Practically, the findings highlight the importance of integrating cyber-ethics education into national curricula, promoting ethics-by-design practices within organisations, and enhancing nationwide digital-ethics awareness campaigns. These implications directly support Malaysia’s aspiration to build a value-driven digital society characterized by integrity, accountability, and respect